Towards More Reliable Renewable Power Systems - Thermal Performance Evaluation of DC/DC Boost Converters Switching Devices - Canras Batunlu; Alhussein Albarbar (Institute of Advanced Engineering and Science, 2015)
Power electronic converters (PECs) are one of the most important elements within renewable power generation systems. The reliability of switching elements of PECs is still below expectations and is a major contributor to the downtime of renewable power generation systems. Conventional technology based elements such as Silicon Insulated Gate Bipolar Transistors (IGBTs) operate as switching components in PECs. Recent topological improvements have led to new devices called Silicon Carbide (SiC) MOSFETs which, are also being used as switching elements for PECs. This paper presents detailed investigations into the performance of those switching devices with a focus on their reliability and thermal characteristics. Namely, trench gate NPT, FS IGBT topologies and SiC MOSFET are firstly modelled using 3-D multi-physics finite element modelling to gain clear understanding of their thermal behaviour. Subsequently, modelling outcomes are verified by using those devices as switching elements in operational boost converters. The purposely-developed test setups are utilised to critically assess the performances of those switching devices under different loading and environmental conditions. In general, SiC device was found to exhibit about 20 °C less in its operating temperature and therefore expected to offer more reliable switching element.